PURWARUPA SISTEM PENGUKURAN DAN PENGENDALIAN KETINGGIAN AIR PADA DAERAH ALIRAN SUNGAI BERBASIS INTERAKSI ARDUINO UNO DAN LABVIEW - , ANGGIT KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this final project has made prototype system water level measurement and control at flow stream area based on Arduino Uno and LabVIEW interaction with 2 ultrasonic sensors SRF05 as measure of water surface distance and servo motor as water gate operator based water level comparison. The first ultrasonic sensor is measuring water surface distance at primary / first stream area and the second ultrasonic sensor is measuring water surface distance at diversion / secondary stream area. Ultrasonic sensor is measuring distance every 1 cm multiple. Distance measured from every ultrasonic sensors state as distance variable. Arduino Uno has sending distance variable 1 and distance variable 2 to LabVIEW. Distance variable 1 and distance variable 2 were converted become water level 1 and water level 2 from calculation process on LabVIEW. Water level 1 and water level 2 were compared and assumed as difference level with calculation water level 1 subtracted water level 2. If water level 1 equal with water level 2 then radian angle of servo motor at 0Â° position and water gate still close. If water level 1 higher than water level 2 then radian angle of servo motor moving at radian angle nÂ° position and water gate open, then water from primary stream area was distributed to diversion stream area. Water gate is open at bottom level, intermediate level and high level accordingly water level comparison condition. Servo motor is controlled in automatic or manual from LabVIEW. Radian Angle of servo motor at every condition is decided by LabVIEW and will be sent to Arduino Uno for moving servo motor.